2020
DOI: 10.1017/s0022029920000977
|View full text |Cite
|
Sign up to set email alerts
|

Shelf life extension of mozzarella cheese packed in preserving liquid with calcium lactate and bergamot juice concentrate

Abstract: Traditional Mozzarella is a fresh cheese produced in Italian local market without additives that shows a short shelf life of about 5 d. This work tested the use of natural additives (bergamot juice concentrate-BJ and calcium lactate-CL) in preserving liquid for a Mozzarella cheese with the aim to extend its shelf life, regarding the microbial growth and overall cheese quality. Results of qualitative analyses showed that the preserving liquid with the mix of BJ and CL promoted an extension of mozzarella shelf l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The results of the ABTS assay, which is better suited to testing both hydrophilic and lipophilic substances, were significantly different (p < 0.01), with higher values in Pizza mozzarella (1.51 ± 0.07 µM TE/g), followed by Mozzarella di Bufala (0.71 ± 0.03 µM TE/g) and Fiordilatte mozzarella (0.68 ± 0.05 µM TE/g). These results are consistent with previous studies on lacto-fermented mozzarella [33]. The antioxidant capacity of milk and its derivatives is due to sulfur-containing amino acids (cysteine), vitamins A and E, carotenoids and enzymatic systems [34].…”
Section: Analyses Of Mozzarella Samplessupporting
confidence: 93%
“…The results of the ABTS assay, which is better suited to testing both hydrophilic and lipophilic substances, were significantly different (p < 0.01), with higher values in Pizza mozzarella (1.51 ± 0.07 µM TE/g), followed by Mozzarella di Bufala (0.71 ± 0.03 µM TE/g) and Fiordilatte mozzarella (0.68 ± 0.05 µM TE/g). These results are consistent with previous studies on lacto-fermented mozzarella [33]. The antioxidant capacity of milk and its derivatives is due to sulfur-containing amino acids (cysteine), vitamins A and E, carotenoids and enzymatic systems [34].…”
Section: Analyses Of Mozzarella Samplessupporting
confidence: 93%
“…A reduction in LAB growth would control the pH of the HMMC samples. Zappia et al [ 26 ] reported the same behavior after using the bergamot juice concentrate in HMMC preserving liquid. It should be noted that in some cases, the inhibition attributable to a single postbiotic was greater than the combined application.…”
Section: Resultsmentioning
confidence: 69%
“…Increasing the shelf life of HMMC due to its high popularity among consumers and increasing distribution is a major issue in the dairy industry. Multiple approaches have been designed to increase the shelf life including active packaging by coatings based on carboxymethyl cellulose and natamycin [ 25 ], active compounds such as potassium sorbate, sodium benzoate, calcium lactate, and calcium ascorbate [ 22 ], or adding bioactive compounds such as bergamot juice concentrate in mozzarella liquid [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the covering liquid is very diverse. It is usually a mixture of brine with mono, divalent salts and/or organic acids (NaCl, CaCl 2 and calcium lactate) [1,[8][9][10]. Kindstedt et al [11] indicated that the phenomenon of generating a fragile surface layer of mozzarella cheese may be related to the calcium content.…”
Section: Introductionmentioning
confidence: 99%